Pengaruh Gaya Hedonisme dan Trend FOMO Terhadap Konsumerisme Belanja Thrifting untuk Memenuhi Gaya Hidup : (Studi Kasus Mahasiswa Fakultas Ekonomi UNUSIDA 2021) - Nur Evika Kamiliyatun Ni'mah; Nur Shinta Devayanti; Indrawan Syah; A Falaqil Isbakhi; Afifatus Sholichah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In today's modern era, there are many various fashion trends, one of which is thrifting, which has become a lifestyle among students. This research aims to analyze the influence of Hedonism and FOMO Style on Thrifting Consumerism among students at the Faculty of Economics, UNUSIDA Class of 2021. This research uses quantitative methods, data is collected using a questionnaire or questionnaire using a random sampling method. In this research, researchers used validity and reliability tests, discriminant validity tests, and hypothesis tests. The results of this research show that there is an influence of Hedonism and FOMO on Thrifting Consumerism among students at the Faculty of Economics, UNUSIDA Class of 2021.